Use of Design Thinking for the Design and Evaluation of a Mobile Nutrition Information Application - Romero, Karoline; Beluomini, Lucas; Scanavacca, Juliana; Pazinatto, Isabella; Balancieri, Renato; Leal, Gislaine; Guerino, Guilherme (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
This paper explores the application of Design Thinking in designing and evaluating a mobile application that provides nutritional information in compliance with the new ANVISA regulations. These regulations establish standards for coloring, contrast, and the location and declaration of nutritional information. We developed a mobile application to simplify the dissemination of nutritional data and highlight allergenic products. The development process followed the Design Thinking methodology, encompassing the stages of empathy, definition, ideation, prototyping, implementation, and testing. An empathy map was created during the empathy phase to understand the target users. In the definition phase, user personas were established. A low-fidelity prototype (wireflow) was created for the ideation phase to visualize the application’s flow and requirements. This phase was followed by the prototyping stage, where high-fidelity prototypes were developed, leading to the initial version of the application. Testing and evaluating this first version were conducted, and the results were analyzed to identify improvements for subsequent application iterations.